Effects of cigarette smoke on the Meckel's cartilage of rat fetus : Morphologic, morphometric and stereologic study - Brandini, Daniela Atili [UNESP]; Sala, Miguel Angel; Lopes, Ruberval Armando; Semprini, Marisa; Contrera, Mary Garcia Duarte (FapUNIFESP (SciELO), 2005)
The purpose of this study was to investigate the effects of cigarette smoke on the development of the embryo mandible (Meckel's) cartilage in rat fetuses. When inhaled by female Wistar rats between the 9th and the 12th day of pregnancy, cigarette smoke (5 cigarettes a day) caused intrauterine growth retardation, providing smaller fetuses and placentas. In fetuses from the experimental group, the histopathologic examination revealed a poorly developed Meckel' s cartilage with smaller chondroblasts showing a scanty cytoplasm with spherical and paler central nuclei, as well as more abundant cartilage matrix. Morphometric analysis revealed that Meckel's cartilage lacunae were smaller in the fetuses from the experimental group, although not showing any remarkable alteration in shape. The results suggested that inhalation of cigarette smoke by pregnant rats during the organogenic period induced growth retardation and delayed cellular differentiation in rat fetal Meckel's cartilage.
Keywords: Cigarette smoke; Meckel's cartilage; Morphometry; Rat fetus; animal; cartilage; female; fetus weight; indoor air pollution; intrauterine growth retardation; mandible; organogenesis; pathology; placenta; pregnancy; prenatal development; rat; three dimensional imaging; Wistar rat; Animals; Cartilage; Female; Fetal Growth Retardation; Fetal Weight; Imaging, Three-Dimensional; Mandible; Organogenesis; Placenta; Pregnancy; Rats; Rats, Wistar; Tobacco Smoke Pollution